Superbugs causing infections at a tertiary care hospital and the return of pre-antibiotic era! - Rajkumar, Kalyan; Radera, Shruti; Agarwal, Jyotsna; Singh, Mastan (Asian Journal of Medical Sciences, 2015)
Aims and Objectives: Increase in the incidence of Escherichia coli and Klebsiella pneumoniae carrying New Delhi metallo beta lactamase-1 (NDM-1) gene are called superbugs is of great concern as presence of blaNDM-1 gene makes E.coli and K.pneumoniae highly resistant to most of currently available antibiotics. This study was planned to observe the burden of blaNDM-1 gene carrying E. coli and K.pneumoniae at a tertiary care hospital in northern India. Materials and Methods: A total of 1709 E. coli and 327 K. pneumonia nonrepitive isolates were taken from various clinical samples received in a tertiary care hospital in northern India Lucknow during the period from May 2012 to April 2013. Carbapenemase production was phenotypically detected in all the carbapenem resistant isolates by modified Hodge test. Metallo-β-lactamase production was detected by using meropenem and imipenem discs with and without EDTA and blaNDM-1 gene was detected by polymerase chain reaction. Results: Over all metallo β- lactamase production was found in 82% and 88.89% of carbapenem resistant E.coli and K. pneumonia respectively. Out of 366 carbapenem resistant isolates, 102 were found positive for blaNDM-1 gene out of which 89 were E.coli and 13 were K. pneumoniae. Conclusions: With limited treatment options left for this crisis situation like the pre-antibiotic era; it is an alarm for rational antibiotic therapy usage and intensive education programs. Asian Journal of Medical Sciences Vol.7(2) 2015 76-79